Addition of spironolactone in patients with resistant hypertension: A meta-analysis of randomized controlled trials - Liping Liu; Bing Xu; Yunfeng Ju (Clinical and Experimental Hypertension, 2017)
This study was designed to assess the effect of additional spironolactone on blood pressure in patients with resistant hypertension. MEDLINE, EMBASE, and Cochrane Library were searched to identify randomized controlled trials (RCTs) that determined the effect of add-on spironolactone on blood pressure in patients with resistant hypertension compared with a control group. A total of five RCTs met the inclusion criteria. Spironolactone reduced office systolic blood pressure (SBP) by 15.73 mmHg (95% CI −20.45 to −11.0; P < 0.00001) and office diastolic blood pressure (DBP) by 6.21 mmHg (95% CI −8.33 to −4.1, P < 0.00001) as compared to placebo group. The pooled changes of 24 h ambulatory or home SBP and DBP were −8.7 mmHg (95% CI −8.79 to −8.62, P < 0.00001) and −4.12 mmHg (95% CI −4.48 to −3.75, P < 0.00001), in favor of the spironolactone group. In comparison with alternative drugs including beta-blocker, candesartan, or alpha methyldopa, spironolactone reduced home SBP by 4.5 mmHg (95% CI −4.63 to −4.37, P < 0.00001). Addition of spironolactone provides benefit effect on blood pressure in patients with resistant hypertension.